Characterization And Acute Toxicity Test Of Black Garlic Ethanol Exctract Based On OECD - Ellen Stephanie Rumaseuw; Yoppi Iskandar; Eli Halimah; Ade Zuhrotun (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Garlic (Allium sativum, L) was used empirically by the ancestors as a useful plant for hypercholesterolemia. The processed garlic product, namely black garlic, has gone through an optimal heating process at a temperature of 70oC for 21 days. Black garlic can become a standardized herb if it has been through characterization and toxicity tests. Methods: The characterization test is known by measuring several general standard parameters of Indonesian extracts. Acute toxicity test was carried out by dividing 5 treatment groups namely negative control, group I (5 mg/kg BW), group II (50 mg/kg BW), group III (300 mg/kg BW), group IV (2000 mg/kg BW). Results: The results showed that the standardization of black garlic extract has a drying shrinkage content of 7.24%, a water content of 8.8%, a total ash content of 4.79%, an acid insoluble ash content of 1.52%, a water soluble extract content of 7.47% and an ethanol soluble extract content of 9.3% which is still into the Indonesian herbal pharmacopoeia standard and the administration of black garlic ethanol extract caused mild toxic symptoms during the acute toxicity test and obtained LD50 values > 2000 mg/kg BW. Conclusion: Characterization of black garlic extract according to standardization parameters of Indonesian plant extracts and administration of ethanolic extract of black garlic has an LD50 value > 2000 mg/kg BW which is included in category 5 in the OECD.